Trends in Manual Brew Coffee Consumption in Indonesia: Preferences, Perceptions, and Consumer Health - Afif, Fuadi; Dwi Nur Laela Fithriya (Gastronary, 2024)
This paper aims to examine the trends in manual brew coffee consumption in Indonesia, focusing on consumer preferences, sensory perceptions, and health impacts. Manual brew methods such as V60, tubruk, and cold brew have become popular choices among urban and millennial consumers, as each offers a unique taste and aroma experience. The study employs a literature review and secondary data analysis to explore the factors influencing consumer preferences, including the sensory characteristics and health benefits of manual brew coffee. The findings reveal that brewing methods like V60 produce a more complex flavour profile, while cold brew offers a smoother taste with lower acidity. Additionally, consumer preferences for manual brew coffee are influenced by awareness of the potential health benefits of coffee consumption. These findings are expected to provide new insights for coffee industry players in developing products and marketing strategies that align with consumption trends in Indonesia.